Phase-locked loop for low frequency application using 0.18um CMOS technology - Zhang, Yao. (2009)
Over the past decade, the desirability of portable operation for all types of electronics system has grown tremendously. The requirement of portability thus places severe restriction on the IC size and power consumption. This leads to the need of scaling. To keep pace with the development of the mixed-signal design, a fully integrated Phase-Locked Loop frequency synthesizer operation with a supply voltage of 1.5 V is explored in this project.